Ending future pandemics: An expert panel discussion - Chaowei Wen; Danli Xie; Xiang Li; Xiaoqun Zheng; Yongliang Lou; Jiahai Lu (​​​One Health Bulletin)
Since the 20th century, global health security related biosafety risks have progressively intensified. Major public health crises, primarily caused by infectious diseases, have become more frequent. Additional concerns, such as population aging, the prevalence of chronic non-communicable diseases like hypertension and diabetes, the growing problem of antimicrobial resistance, and the ongoing effects of global environmental changes and worsening air pollution, have increased health risks for humanity. One Health, a multidisciplinary and cross-regional collaboration strategy that encompasses human, animal, and environmental health care, has become a key internationally recognized strategy for addressing significant and complex human health issues. On April 2, 2024, the One Health Innovation and Development Forum was held at Wenzhou Medical University. At this forum, experts from around the world gathered to discuss topics such as infectious disease prevention and control, vaccine development, antibiotic resistance, food safety, and environmental health. They reached a consensus and took action to jointly promote the realization of a global community of health for all.